Factors influencing infestation of fruit-fly (Carpomyia vesuviana) in indian jujube (Zizyphus mauritiana) - SINGH, M P; VASHlSHTHA, B B (The Indian Journal of Agricultural Sciences, 2014)
An investigation was carried out during 1995-99 at Jodhpur in the Indian arid region, to study the influence of physical, biochemical and physiological factors on the infestation of ber fruit-fly (Carpomyia vesuviana Costa) on fruits of different cultivars of indian jujube (Ziziphlls mauriliana Lamk.). Fruit size, fruit weight and pulp: stone ratio exhibited positive correlation with fruit-fly infestation (%). Cultivars with round fruits contracted greater fruit-fly infestation. Fruit texture did not influence the extent of fruit-fly infestation in indian jujube, though cultivars (’Ponda’ and ’Umran’) with hard fruit texture showed lower infestation (42 and 31%). Total soluble solids had small but inverse relationship (r= -0.1583) with per cent fruit-fly infestation. Acidity and vitamin C content exhibited negative (r = -0.235) and small positive (r = 0.1996) correlation, respectively, with fruit-fly infestation (%). Greater fly infestation was recorded in cultivars in which fruit set occurred early in .the season. The early" maturing cultivars (’Gola’, ’Jogia’, ’Mundia’ and ’Seb’) Contracted higher fruit-fly infestation (75,54,56 and 53%) compared to those maturing late. Interrelationship among various factors exhibited positive correlation coefficient. (r) values between fruit size and fruit weight (0.8394), fruit size and PSR (0.3069), fruit weightand PSR, TSS and vitamin C (0.1213), acidity and vitamin C (0.2640) and TSS and acidity (0.3460).